Growing Teratoma Syndrome After Chemotherapy For Ovarian Immature Teratoma. Issue 7 (October 2020) - Imran, Hamayun; Siddiqui, Abdul H.; Wilson, Felicia; Pashankar, Farzana
Abstract : The management of ovarian immature teratoma (IT) presents several challenges. It occurs both in children and adults and therefore is managed by pediatric oncologists as well as adult and gynecologic oncologists. Treatment approach; however, varies significantly. Unlike pediatric patients in whom surgery is considered the mainstay of treatment, adult providers routinely prescribe postoperative chemotherapy. Management of recurrent IT can be challenging. Growing teratoma syndrome may occur after treatment of recurrent IT. We report the development and management of this phenomenon in a pediatric patient who had several recurrences of her IT.